Diversidad de helechos y licófitas de la Reserva Natural Punta Lara, Buenos Aires, Argentina - Giúdice, Gabriela Elena (2011)
Punta Lara Natural Reserve shelters the relict of the Southernmost riparian forest in the world, where the flora is threatened by the anthropic expansion and by the introduction of exotic species. In this area the ferns and lycophytes grow in particular environments as marshland, grassland and marginal forest. The aim of this work was to evaluate the diversity of ferns and lycophytes that inhabit in Punta Lara Natural Reserve. Field trips were conducted from 2006 to 2009 and local herbaria and specific bibliography were also revised. As a result of our study twenty four taxa of ferns and lycophytes were recognized. Their habit was mainly terrestrial (70%), fewer aquatic (17%) and epiphytic (13%). Five native taxa were scarcely recorded whereas two native species previously documented were not found. We assume that the main threats on ferns and lycophytes populations in Punta Lara Reserve are: removal for comercialization, invasion by exotic species and climatic fluctuations (drought periods). Keys for taxa identification are given and strategies for the conservation of threatened taxa are proposed.